MBOJO NICKNAMES: REVIEWING THE CLIPPING PROCESS OF BIMANESE PERSONAL NAMES - Gusdian, Rosalin Ismayoeng; Zuhra, Azizatul (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
It is the aim of the study to reveal the distinctive clipping process that takes place in the word formation of nicknames in Mbojo which is one of the major ethnic groups in Bima and its surroundings. Moreover, this study employed qualitative method. The objects of this current study were Mbojo nicknames used by people who live in Dompu Regency, West Nusa Tenggara.Â  The nicknames were collected from the family cards (KK), in 2 community units (RW). The data were supported by an informant who is a native of Dompu regency was requested to validate and check whether the collected nicknames data were truly the local people. In analyzing the data, the researcher classified the collected data using the categorization of clipping process. The result of the study showed that the clipping process found in Mbojo nicknames took place in the beginning of the names (fore-clipping); in the end of the names (back-clipping); in the beginning and end of the names (ambi-clipping); in the middle and end of the names (median-clipping and back-clipping); and in the beginning, middle, and end of the names (fore-clipping, median-clipping, and back-clipping). It is implicated that among these clipping process, ambi-clipping is the most frequently found type in Mbojo nicknames.